1992
DOI: 10.1152/jappl.1992.73.3.1084
|View full text |Cite
|
Sign up to set email alerts
|

PAF antagonists inhibit pulmonary vascular remodeling induced by hypobaric hypoxia in rats

Abstract: Chronic hypoxia causes pulmonary hypertension and pulmonary vascular remodeling in rats. Because platelet-activating factor (PAF) levels increase in lung lavage fluid and in plasma from chronically hypoxic rats, we examined the effect of two specific, structurally unrelated PAF antagonists, WEB 2170 and BN 50739, on hypoxia-induced pulmonary vascular remodeling. Treatment with either agent reduced hypoxia-induced pulmonary hypertension and right ventricular hypertrophy at 3 wk of hypoxic exposure (simulated al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 0 publications
2
47
0
1
Order By: Relevance
“…It has been reported that the ROS generated by hypoxia can induce calcium release from sarcoplasmic reticulum stores, followed by pulmonary vasoconstriction. 5 Moreover, ROS activated VEGF, 4 PAF, [7][8][9] and MAPK, 10 which induced vascular remodeling. PAF subsequently induced oxidative bursts in macrophages, which might cause a vicious circle to advance the process of pulmonary vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the ROS generated by hypoxia can induce calcium release from sarcoplasmic reticulum stores, followed by pulmonary vasoconstriction. 5 Moreover, ROS activated VEGF, 4 PAF, [7][8][9] and MAPK, 10 which induced vascular remodeling. PAF subsequently induced oxidative bursts in macrophages, which might cause a vicious circle to advance the process of pulmonary vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…ROS upregulates expression of several factors to modify vascular remodeling, such as vascular endothelial growth factor (VEGF), 4 plateletactivating factor (PAF), [7][8][9] and mitogen-activated protein kinase (MAPK). 10 Thus, several intrinsic substances to modulate pulmonary ROS levels may play protecting or aggravating roles in progression of pulmonary vascular remodeling.…”
mentioning
confidence: 99%
“…These findings suggest that EGFR plays a role in fetal ovine pulmonary vascular remodeling following long-term HAH and that inhibition of EGFR signaling may reverse high altitude-induced pulmonary vascular remodeling. Similar to EGFR, platelet-activating factor (PAF) and PAF receptor have also been implicated in the pathogenesis of long-term HAH-induced pulmonary remodeling and hypertension in different animal models [56,57]. In those studies, high PAF and PAF receptor expression levels in the pulmonary arteries have been reported in the long-term hypoxia-exposed animals [56,57].…”
Section: Pulmonary Vascular Systemmentioning
confidence: 97%
“…Similar to EGFR, platelet-activating factor (PAF) and PAF receptor have also been implicated in the pathogenesis of long-term HAH-induced pulmonary remodeling and hypertension in different animal models [56,57]. In those studies, high PAF and PAF receptor expression levels in the pulmonary arteries have been reported in the long-term hypoxia-exposed animals [56,57]. Furthermore, PAF receptor antagonists attenuated hypoxia-induced pulmonary hypertension and pulmonary vascular remodeling [56], suggesting that PAF receptor-mediated signaling also plays a key role in pulmonary vascular remodeling.…”
Section: Pulmonary Vascular Systemmentioning
confidence: 99%
“…It has been reported that ROS generated by hypoxia can induce calcium release from sarcoplasmic reticulum stores, which is followed by pulmonary vasoconstriction (Waypa et al, 2002). Moreover, ROS activated several growth factors such as vascular endothelial growth factor and platelet-activating factor (PAF) (Hartung et al, 1983;Ono et al, 1992;Chandel et al, 1998), which induce vascular remodeling. In the early phase of hypoxic conditions, ROS may act as a trigger of this signaling cascade in the process of vascular remodeling.…”
Section: Wwwintechopencommentioning
confidence: 99%